Implementasi Media Android Kepada Calon Guru, Guru SMA dan MA di Kabupaten Indramayu - Gunadi, Farid; Dadang Juandi; Rizki Dwi Siswanto; Sholikhakh, Rizqi Amaliyakh; Saputri, Veni; Kusumah, Yaya S.; Dasari, Dadan (Jurnal SOLMA, 2025)
Background: Based on observations and interviews with teachers and grade XII students, it was found that students still have difficulty understanding mathematics. This is due to the lack of creativity of teachers in creating technology-based learning media. Method: This community service activity aims to provide solutions through simulations and focus group discussions (FGD) on the use of Android-based learning media. FGD participants consisted of 11 teachers and 3 prospective teachers from high schools and Islamic high schools in Indramayu. The activity was carried out through direct simulations and discussions, with data collection using questionnaires that were analyzed through the validity test of the Aiken and Atlas-ti indexes. Results: The results showed that Android media met the aspects of content quality, learning, and technical aspects with the category of "feasible" (average score of 3.454).  Conclusion: The application was declared feasible for use in learning, although it still needs further development according to participant input.